Efeitos do pré-condicionamento por oxigenoterapia hiperbárica na lesão de isquemia e reperfursão em ratos - Cristiano Xavier Lima (2006)
Liver ischemia/reperfusion injury (IR injury) is a cellular and immunological insult. It occurs in various clinical situations in which blood flow to the liver is interrupted. Hyperbaric oxygenation (HO) has been used as a treatment option in several ischemic diseases. Howeverthe effectiveness of this method as protective against IR injuries is controversial. To determine the effect of HO in IR liver injury, a model of partial warm liver ischemia was used. Hilar area of the left lateral and medial hepatic lobes were clamped for 30 minutes followed by 30 reperfusion. For the study was conducted on 32 male Wistar rats which divided into four groups of eight animals each: group A animals submitted to laparotomy and liver manipulation, group B animals submitted to IR, group C animals pre-treated with 90 minutes of HO before IR and group C animals pre-treated with room air at 2,5 atm absolute before IR. Before ischemia episode and after 30 minutes of reperfusion, plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehidrogenase (LDH) analyses wereperformed. Intra-arterial blood pressure was monitored continuously. Myeloperoxidase (MPO) activity in liver and lung were assessed after 30 minutes of reperfusion. AST, ALT and LDH increased after reperfusion in all the animals. ALT values and MPO activity in the liver parenchyma of HO pre-treated animals were higher than in groups A,B and D. Lung parenchyma MPO activity was higher in HO treated animal groups C and D. HO had negative hemodynamic effects during liver IR. We conclude that liver preconditioning with HO aggravated liver IR injury in rats.